Substance use disorders in Saudi Arabia: a scoping review - Nazmus Saquib; Ahmad Mamoun Rajab; Juliann Saquib; AbdulRahman AlMazrou (BMC, 2020)
Abstract Background Substance use disorders (SUD) are mental health conditions that arise from chronic drug use. There is an increased recognition of this problem in Saudi Arabia. Objective Conduct a comprehensive review of published literature on SUD to identify knowledge gaps and to guide future research. Methods PubMed, Embase and Cochrane databases were searched with suitable keywords for SUD publications up to June 10, 2019. Eligible studies (primary research conducted in Saudi Arabia) were organized into three broad domains: (1) risk (or protective) factors of SUD, (2) perspectives on drug use of people who use drugs, and (3) impact on family. The quality of the included studies was assessed with the Newcastle-Ottawa Scale. Results Of the 113 search records, 23 were eligible for analysis (19 cross-sectional and 4 case-control). All studies were conducted in clinical settings; all but two included males only. There were 4 studies about SUD risk factors, 6 studies about the perspectives of people who use drugs, and none about family impact. None of the cross-sectional studies (0%) and 25% of case-control studies were of good quality. Conclusions The available studies were few in number, weak in methodology, and poor in quality. Quantitative as well as qualitative studies about SUD are warranted in each domain and should represent both genders.